Analisis Audit Operasional Terhadap Kualitas Pelayanan (Studi Kasus Pada PT. Jiwasraya (Persero) Regional Office II -Bandung) - Syamsul Huda; Irvan Yoga Pardistya (Accounthink, 2017)
The purpose of this research is to analyze the phenomena that happens in PT. Jiwasraya (Persero) Regional Office II, Bandung by assessing the impact of operational audit to the service quality. The approach used in collecting the information related to the problem is the alternative approach, using direct and indirect information. Based on the nature, this research is categorized as explanatory research by analyzing quantitative data and qualitative analysis to obtain the answer. Therefore, the method used in this research is non-probability sampling with saturation sampling technique. As for the variable testing examined, correlation technique is used to calculate the correlation and the linear regression in order to assess the correlation and impact between variables. The testing of the hypothesis uses t-test. With the significance degree of 5% (?=0,05), the two-sided t table of 2,048 is obtained. Since t is 2, 958 > t table = 2,358, then Ho is rejected and Ha is accepted. Thus, based on the test result with the level of confidence of 95%, operational audit has a positive and significant impact to the service quality in PT. Jiwasraya (Persero) Regional Office II, Bandung. The degree of correlation coefficient between variables is 46,2%, which is medium. Meanwhile, the coefficient of determination shows the number of 52,6%, which means the operational audit has a strong impact to the service quality, and the other 47,6% is affected by other factors outside this research (operational audit).